Cover Image. Issue 8 (1st August 2022) - Schultz‐Rogers, Laura E.; Thayer, Michelle L.; Kambakam, Sekhar; Wierson, Wesley A.; Helmer, Jordan A.; Wishman, Mark D.; Wall, Kristen A.; Greig, Jessica L.; Forsman, Jaimie L.; Puchhalapalli, Kavya; Nair, Siddharth; Weiss, Trevor J.; et al.
Abstract : Immunolabeled tissue section of 3‐day zebrafish embryo, double mutant for the tumor suppressor Rb and chromatin adaptor Rbbp4, showing programmed cell death (green), neurons (red), and nuclei (blue) in the retina and brain. From: Rbbp4 loss disrupts neural progenitor cell cycle regulation independent of Rb and leads to Tp53 acetylation and apoptosis ; Schultz‐Rogers LE, et al. https://doi.org/10.1002/dvdy.467